LANGUAGE IDENTITY AND ITS FACTORS - Matluba Turdieva (Galaxy International Interdisciplinary Research Journal, 2024)
Communication is among the first terms that spring to mind when discussing language. Conversely, language is an essential component of identity and for all forms of communication with the outside world. Identity is a projection of who you are onto the world and how other people see you. Furthermore, because identity development involves people making conscious decisions that alter who they are, it calls for a certain amount of awareness. Family, peer relationships, and physical location are three elements that shape language and identity over the course of a person’s life. In order to demonstrate how identity is not static but rather changes over time because of this relationship, this article will describe it and provide some examples of identity in language use.